Evaluation of stiffness derivative for a delta wing with straight leading edges in unsteady flow - Renita, Sharon Monis; Crasta, Asha; Khan, Sher Afghan (Blue Eyes Intelligence Engineering & Sciences, 2019)
The emphasis of this paper is to examine the Stiffness derivative variation with the pivot position by varying Mach number in unsteady flow and its comparison with quasi-steady the flow of Crasta& Khan for varying angle of attack with different Mach number. From the results, it is evident that Stiffness derivative decreases as the Mach number increases. Comparison with Liu as well as Crasta& Khan theory it is evident that there is an improvement in the present theory being unsteady over quasi-steady theory, in addition to the fact that in the present work the pressure on the leeward surface is taken into account which results in increased value of the stability derivative and the same is clearly visible in results